2015
DOI: 10.3923/rjmp.2015.90.104
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Studies on the Antileishmanial Activity of Herbicides and Plant Extracts Against Leishmania major Parasites

Abstract: Natural products and herbicides are potential sources of new and selective agents for the treatment of important tropical diseases caused by parasites. Leishmaniasis is a major health problem worldwide and affects millions of people especially in developing nations. There is no immunoprophylaxis (vaccination) available for Leishmania infections and conventional treatments are unsatisfactory. Therefore, antileishmanial drugs are urgently needed. In this study, the antileishmanial activity of two herbicides (acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…To assess the potential for leishmaniasis treatment, we calculated the selectivity index (SI) by determining the ratio between the cellular cytotoxicity (CC 50 ) of macrophages and the IC 50 of leishmaniasis. An SI greater than 1 suggests the potential for treating leishmaniasis [ 29 ]. Interestingly, both the extract and the fraction had a selectivity index greater than 8.6 and 12.4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the potential for leishmaniasis treatment, we calculated the selectivity index (SI) by determining the ratio between the cellular cytotoxicity (CC 50 ) of macrophages and the IC 50 of leishmaniasis. An SI greater than 1 suggests the potential for treating leishmaniasis [ 29 ]. Interestingly, both the extract and the fraction had a selectivity index greater than 8.6 and 12.4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that PB had a significant antiparasitic effect against multiple parasite species such as Schistosoma mansoni [16], Leishmania sp. [17], and Plasmodium berghei infected malaria [18], as it can act as electrons acceptor that competes with the CoQ in the electron transport chain [19]. Because of the few reported studies about the antiparasitic effect of PB against F. gigantica.…”
Section: Introductionmentioning
confidence: 99%